A review of the milliped genus Haplogonopus with commentary on the so-called “Charactopygus-Bildung” modification of spirostreptid paraprocts (Diplopoda: Spirostreptidae) - Hoffman, Richard L. (Zootaxa, 2011)
The status of the monotypic taxon Haplogonopus (Verhoeff, 1941), proposed for a disjunct Tanzanian spirostreptoid, is reviewed in light of two additional species, which despite different peripheral appearances, are referable to this genus on the basis of genitalic features. Haplogonopus inflatannulus Verhoeff is redescribed from topotypic material, the nominal species Charactopygus jeanneli (Brolemann, 1920) is relocated in Haplogonopus (n. comb.), and the new species H. cin- gulatus is described from the Rondo Plateau in southeastern Tanzania. A terminology for the modified paraproct structure (“Charactopygus-Bildung”) of spirostreptids is proposed.